Chronic obstructive pulmonary disease and atrial fibrillation: an interdisciplinary perspective. (18th November 2020) - Simons, Sami O; Elliott, Adrian; Sastry, Manuel; Hendriks, Jeroen M; Arzt, Michael; Rienstra, Michiel; Kalman, Jonathan M; Heidbuchel, Hein; Nattel, Stanley; Wesseling, Geertjan; Schotten, Ulrich; van Gelder, Isabelle C; et al.
Abstract: Chronic obstructive pulmonary disease (COPD) is highly prevalent among patients with atrial fibrillation (AF), shares common risk factors, and adds to the overall morbidity and mortality in this population. Additionally, it may promote AF and impair treatment efficacy. The prevalence of COPD in AF patients is high and is estimated to be ∼25%. Diagnosis and treatment of COPD in AF patients requires a close interdisciplinary collaboration between the electrophysiologist/cardiologist and pulmonologist. Differential diagnosis may be challenging, especially in elderly and smoking patients complaining of unspecific symptoms such as dyspnoea and fatigue. Routine evaluation of lung function and determination of natriuretic peptides and echocardiography may be reasonable to detect COPD and heart failure as contributing causes of dyspnoea. Acute exacerbation of COPD transiently increases AF risk due to hypoxia-mediated mechanisms, inflammation, increased use of beta-2 agonists, and autonomic changes. Observational data suggest that COPD promotes AF progression, increases AF recurrence after cardioversion, and reduces the efficacy of catheter-based antiarrhythmic therapy. However, it remains unclear whether treatment of COPD improves AF outcomes and which metric should be used to determine COPD severity and guide treatment in AF patients. Data from non-randomized studies suggest that COPD is associated with increased AF recurrence after electrical cardioversion and catheter ablation. Future prospective cohort studies in AF patients are needed to confirm the relationship between COPD and AF, the benefits of treatment of either COPD or AF in this population, and to clarify the need and cost-effectiveness of routine COPD screening.